2022
DOI: 10.21203/rs.3.rs-1462289/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ziyuglycoside I attenuates collagen-induced arthritis through restoring the balance of Th17/Treg cells

Abstract: Objective: To investigate the therapeutic effect and primary pharmacological mechanism of Ziyuglycoside I (Ziyu I) on collagen-induced arthritis (CIA) mice. Methods: CIA mice were treated by 5, 10, or 20 mg/kg of Ziyu I or 2 mg/kg of methotrexate (MTX), and clinical manifestations as well as pathological changes were observed. T cell subsets were determined by flow cytometry. T cell viability was measured by CCK-8. The expressions of transforming growth factor beta (TGF-β) and IL-17 in serum were detected by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…[116,119,120] It was found that columbianadin can inhibit the differentiation of CD4 T lymphocytes towards th17 cells and promote their differentiation towards treg cells in CIA mice and the spleen lymphocytes of balb/c mice. [91] Our meta-analysis indicated that DJD treatment could better improve the level of CD4 + , CD8 + , and CD4 + / CD8 + than rDMARDs. However, further research is necessary to confirm the efficacy of these aspects, as limited data (including 140 patients in the treatment and control groups) may lead to false positive results.…”
Section: Principal Findingsmentioning
confidence: 72%
See 1 more Smart Citation
“…[116,119,120] It was found that columbianadin can inhibit the differentiation of CD4 T lymphocytes towards th17 cells and promote their differentiation towards treg cells in CIA mice and the spleen lymphocytes of balb/c mice. [91] Our meta-analysis indicated that DJD treatment could better improve the level of CD4 + , CD8 + , and CD4 + / CD8 + than rDMARDs. However, further research is necessary to confirm the efficacy of these aspects, as limited data (including 140 patients in the treatment and control groups) may lead to false positive results.…”
Section: Principal Findingsmentioning
confidence: 72%
“…[90] Similarly, it was found that columbianadin can inhibit the secretion of the inflammatory cytokine IL-17A, promote its differentiation towards treg cells, and promote the secretion of anti-inflammatory cytokines. [91] Several studies have revealed that osthole, an active ingredients of Radix Angelicae Pubescentis (Du Huo), can inhibit the proliferation, migration, and invasion of RA fibroblast like synovial cells by weakening NF-κB signaling, [92] and activate AMPK to inhibit NLRP3 inflammasome activation. [93] Additionally, many inflammatory factors, including IL-1β, IL-6, TNF-α, etc., were found to be decreased by active ingredients or extracts in DJD in both in vivo and in vitro experiments of RA, such as senkyunolide I, [94] 18β-Glycyrrhetinic acid, [95] liquiritin, [96] polysaccharide from Radix Angelicae sinensis (Dang Gui), [97] paeoniflorin, [98][99][100][101][102] paeoniflorin-6'-O-benzene sulfonate, [103] curcumin, [104] the total saponins of Radix Achyranthis bidentatae (Niu Xi), [105] supercritical carbon dioxide extraction of Radix Achyranthis bidentatae (Niu Xi), [106] polysaccharide from Radix Saposhnikoviae divaricatae (Fang Feng), [107,108] and Radix Saposhnikoviae divaricatae (Fang Feng).…”
Section: Principal Findingsmentioning
confidence: 99%